Oxygen Manifesto - "Mishra, Atulya" (New Delhi, 2019)
Oxygen manifesto is a story of the triumph of ordinary people over the might of the establishment in their battle to save the environment. Thatha lives in a remote and inaccessible part of Manipur and Ravi is a young IAS Officer from the Tamil Nadu Cadre. Circumstances bring them together and they create the most effective environmental movement the world has ever seen.
Keywords: English - Fiction